TPACK Mastery through STEM-Integrated Project-Based Learning in Online Physics Course - Irma Rahmawati; Siti Noor Latifah; Bakhrul Rizky Kurniawan (Yayasan Nurul Yakin Bunga Tanjung, 2026)
This study investigates the effectiveness of STEM-integrated project-based learning (PBL) in enhancing prospective physics teachers' TPACK mastery within an online multimedia physics course. Employing a mixed-methods embedded design, 18 prospective physics teachers at Universitas Islam Negeri Antasari Banjarmasin engaged in a five-stage STEM-PBL framework reflection, research, discovery, application, and communication via a learning management system, culminating in educational video projects and lesson plans assessed using a validated TPACK rubric. Descriptive analysis revealed that the majority of students (67.1%) attained moderate TPACK proficiency, with 16.7% achieving high and 22.2% low categories. Although female students demonstrated marginally higher mean scores (M = 82.1) compared to males (M = 81.8), Mann-Whitney tests confirmed no statistically significant gender differences across any TPACK dimension (p > 0.05). These findings contribute empirical evidence that STEM-integrated PBL delivered through online platforms effectively fosters technological, pedagogical, and content competencies among prospective teachers, addressing the growing demand for digitally competent educators. The study underscores the pedagogical value of structured, project-based approaches in teacher preparation programs and offers practical implications for designing online learning environments that integrate STEM principles to develop 21st-century teaching competencies.